2021
DOI: 10.31186/jspi.id.16.1.26-33
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Telur Puyuh yang Diberikan Ransum dengan Penambahan Silase Tepung Daun Ubi Kayu

Abstract: Egg is a product from the poultry which has a high nutrition value and easy to be digested. The research aimed to evaluate the impact of using silage of cassava leaves in a form of mash ration on the quail eggs. The experimental design consisted of 4 treatments and 4 replications. In addition, each replication consisted of 4 quails. The treatments were T0 (ration + silage of cassava leaves 0%), T1 (ration + silage of cassava leaves 3%), T2 (ration + silage of cassava leaves 6%), T3 (ration + silage of cassava … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The positive effect of giving probiotics in the ration on shell weight is being able to reduce the number of damaged eggs, due to the sturdy shell shape. The average shell weight which tended to increase due to probiotic supplementation in the rations in this study was similar to the results of the study by [31] that administration of probiotics tends to increase the average eggshell weight.…”
Section: External Quality Of Eggssupporting
confidence: 90%
See 1 more Smart Citation
“…The positive effect of giving probiotics in the ration on shell weight is being able to reduce the number of damaged eggs, due to the sturdy shell shape. The average shell weight which tended to increase due to probiotic supplementation in the rations in this study was similar to the results of the study by [31] that administration of probiotics tends to increase the average eggshell weight.…”
Section: External Quality Of Eggssupporting
confidence: 90%
“…Sahid et al [31] reported the results of their study that the addition of the probiotic Lactobacillus salivarius to the diet can increase the weight of albumin in quail eggs, because probiotic bacteria can stimulate the growth of intestinal villi to get longer, so that the surface of the absorption area can absorb food and substances in the intestine [32].…”
Section: External Quality Of Eggsmentioning
confidence: 99%
“…Meanwhile, according to quail eggs are foods rich in protein. (Amirul, 2016) (Satria et al, 2021) Figure 8 : Nutritious Feeding Filling out the questionnaire is the last activity in this activity. From the results of filling out questionnaires conducted by students, it was found that students felt very happy with this service activity.…”
Section: Implementation Methodsmentioning
confidence: 99%
“…Quail eggs are one of the high food sources of protein, which is 13.20% (Lokapirnasari, 2017). Based on the physical composition, quail eggs consist of 31.90% yolk, 47.40% egg albumen, and 20.70% eggshells (Satria et al, 2021).…”
Section: Introductionmentioning
confidence: 99%